PERSONAL HYGIENE COUNSELING AS AN EFFORT TO PREVENT INFECTIOUS DISEASES IN ELEMENTARY SCHOOL CHILDREN IN KOTO MASJID VILLAGE - Salim, Agus; Neni Afriyani; Dian Fetri Harahap (LPPM Universitas Awal Bros, 2026)
ABSTRACT Koto Masjid Village is a village in Koto Kampar District XIII, with a fairly busy community. One important aspect of maintaining public health is instilling clean and healthy lifestyle habits from an early age in elementary school-aged children. In response to this situation, the author initiated the